Effects of ICT-Based Instructional Approach on In-Service Teachers’ Attitude toward Classroom Integration and Students’ Learning Outcomes in Basic Technology (2014)
Available studies have substantiated the effectiveness of ICT-based instructional approach on students‘ learning outcomes in other school subjects but it is rarely used among Junior Secondary School (JSS) students in Ogun State in particular due to teachers‘ poor attitude to classroom integration. This study, therefore, determined the effects of ICT-based instructional approach on in-service teachers‘ attitude to classroom integration and students‘ learning outcomes in basic technology in Junior Secondary Schools in Ogun State. The study adopted pretest- posttest, control group, quasi- experimental design with 2x2x2 factorial matrix with two phases. Purposive sampling technique was used in the first phase to select 29 teachers from 12 JSS while in the second phase, intact classes of 205 JSS 2 students from six purposively selected secondary schools in Ijebu-East Senatorial District. The experimental and control groups in the first phase were exposed to classroom integration of ICT-based and conventional instructional approaches while those in the second phase were also exposed to ICT-based and conventional instructional resources. Each treatment was for six weeks. Instructional Guides for Teachers and Students were the two stimulus instruments used. In addition, five response instruments used were: In-service Teachers‘ Attitude to ICT Integration Scale (r = 0.81), In-service Teachers‘ Computer Attitude Scale (r = 0.80), Students‘ Academic Achievement Test in Basic Technology (r = 0.76), Students‘ Attitude towards Basic Technology Scale (r = 0.79) and Students‘ Computer Attitude Scale (r = 0.87). Seven hypotheses were tested at 0.05 level of significance in each of the two phases, using Analysis of Covariance. There was significant main effect of ICT-based instructional resources on students‘ achievement in (F (1,196) =18.27; R2 = 0.142) and attitude to (F (1,196) = 4.100; R2 = 0.021) basic technology. There was no significant main effect of students‘ computer attitude and gender respectively on students‘ achievement in and attitude to basic technology. There was also no significant interaction effect of students‘ computer attitude and gender on students‘ achievement in and attitude to basic technology. There was no significant main effect of ICT-based instructional approach on teachers‘ attitude to classroom integration. There was also no significant main effect of teachers‘ computer attitude and gender on their attitude to classroom integration respectively. Further, there was no significant interaction effect of teachers‘ computer attitude and gender on their attitude to classroom integration. ICT-based instructional resources enhanced students‘ achievement in and attitude to basic technology. Sustainable ICT-based resources should be provided and used to promote ICT-based instructional approach in basic technology classrooms to enhance better learning outcomes.